2012
DOI: 10.1073/pnas.1120473109
|View full text |Cite
|
Sign up to set email alerts
|

Sex-lethal enables germline stem cell differentiation by down-regulating Nanos protein levels during Drosophila oogenesis

Abstract: Drosophila ovarian germ cells require Sex-lethal (Sxl) to exit from the stem cell state and to enter the differentiation pathway. Sxl encodes a female-specific RNA binding protein and in somatic cells serves as the developmental switch gene for somatic sex determination and X-chromosome dosage compensation. None of the known Sxl target genes are required for germline differentiation, leaving open the question of how Sxl promotes the transition from stem cell to committed daughter cell. We address the mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
97
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(102 citation statements)
references
References 45 publications
5
97
0
Order By: Relevance
“…Bam is necessary and sufficient for GSC differentiation (McKearin and Ohlstein, 1995;McKearin and Spradling, 1990;Ohlstein and McKearin, 1997). Mechanistically, Bam is recruited to its target mRNAs through direct binding or its RNA-binding partners, such as Bgcn and Sxl, to repress target mRNA translation (Chau et al, 2009(Chau et al, , 2012Li et al, 2009Li et al, , 2013. Bam works with Smurf to repress BMP signaling in GSC progeny by unknown mechanisms (Casanueva and Ferguson, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Bam is necessary and sufficient for GSC differentiation (McKearin and Ohlstein, 1995;McKearin and Spradling, 1990;Ohlstein and McKearin, 1997). Mechanistically, Bam is recruited to its target mRNAs through direct binding or its RNA-binding partners, such as Bgcn and Sxl, to repress target mRNA translation (Chau et al, 2009(Chau et al, , 2012Li et al, 2009Li et al, , 2013. Bam works with Smurf to repress BMP signaling in GSC progeny by unknown mechanisms (Casanueva and Ferguson, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Cell-intrinsic programs, such as those carried out by the translational repressor Nanos, are also required for stem cell maintenance (Forbes and Lehmann, 1998;Gilboa and Lehmann, 2004;Harris et al, 2011;Wang and Lin, 2004). Following an oriented cell division, the GSC daughter that is specified as a CB displays an increase in Bam protein levels and a decrease in self-renewal factors, including Nanos protein (Chau et al, 2009(Chau et al, , 2012Li et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We recently found that the switch to the CB fate requires the female-specific RNA-binding protein Sex lethal (Sxl) (Chau et al, 2009(Chau et al, , 2012. Germ cells without Sxl protein form tumors that comprise a few bona fide GSCs located at the tip of the germarium and cells that coexpress both Bam protein and a set of GSC markers, including Nanos protein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identity of Sxl target genes in the germ line is not well characterized; however, a recent study indicates that nanos, a gene required for GSC maintenance, is a Sxl target (7). Indeed, Sxl has been proposed to promote the differentiation of GSCs by downregulating Nanos levels in CBs by binding to the nanos 3′ UTR (7). In addition, Sxl is also important for repressing the expression of testis-specific genes, including Phf7, a male germline identity gene (8).…”
mentioning
confidence: 99%